The meso-level interplay of climate and disaster risk management in Viet Nam - Le Duc Ngoan; Le Thi-Hoa-Sen; Nguyen Thi Thanh Huong; Ian Christoplos (Danish Institute for International Studies (DIIS), 2016)
Goals for climate change adaptation and disaster risk management are widely recognised as overlapping, but little is known about the dynamics of this interplay in the perspectives and practices of local authorities. An important aspect of this is how provincial, district and municipal level institutions comprehend and operationalise climate change adaptation frameworks against the backdrop of their past experience of responding to disasters. This is in turn related to how they provide services to risk prone populations. This research report describes how meso-level institutions in Viet Nam mediate between the different intentions and priorities embodied in national climate change and disaster risk management policies, and ongoing efforts of individual households and communities to adapt to environmental change and natural hazards. Research findings suggest that they are doing this in a context wherein past assumptions about the role of the state are being questioned, but where answers remain ambiguous. Findings emphasise the process of 'bricolage' that is underway, wherein different disaster risk and climate goals, rules and structures are combined. Some of these institutional changes involve innovation and others reflect path dependencies anchored in past societal roles.
Keywords: 300